Financial management of health care organizations : an introduction to fundamental tools, concepts, and applications - Zelman, William N.; McCue, Michael J. (Michael Joseph), 1954-; Glick, Noah D.; Thomas, Marci S., 1953- (Jossey-Bass, 2014)
Of Newport Hospital's Ratios.